PELATIHAN PENCAK SILAT PUTRA SETIA DALAM MENINGKATKAN KARAKTER RELIGIUS ANAK DI DESA SIRNAJATI - Febriyanto, Febriyanto; Haqiyah, Aridhotul; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2024)
The community service programme in improving children's religious character through pencak silat putra setia in Sirnajati Village was carried out to help build children's religious character through Pencak Silat training activities and teaching Islamic religious values. The target target of active participants is 25 children from Madrasah Diniyah Takmiliyah Awaliyah, this programme lasts for one month, from 17 February to 3 March 2024. The service method applies socialisation and training with pencak silat training activities twice a week. Through a series of planned activities, the programme succeeded in improving participants' Pencak Silat technique skills and understanding of Islamic values. The programme evaluation showed a significant positive impact, but further steps are needed such as maintaining programme continuity, improving participant evaluation, involving related parties, and diversifying materials to increase its effectiveness in the long term. It is hoped that this programme can continue to make a sustainable contribution to the religious character building of Sirnajati Village children.